SARS-CoV-2 detection in pregnant and non-pregnant women - Noor Hazim Abdulkareem; Elham Hazeim Abdulkareem (IMR Press, 2021)
Background: The coronavirus causing severe acute respiratory syndrome has infected over 2 million people worldwide, killed thousands, and triggered a global pandemic. There is a scarcity of information about pregnant and non-pregnant women who have coronavirus disease (COVID-19). This study's aim was to determine whether the severe acute respiratory syndrome coronavirus 2 was present in the vaginal fluid of infected women. Also, their platelet counts were examined to see whether they were higher in severe versus moderate cases of the COVID-19 disease. Methods: Our Obstetrics Clinic treated 31 women with confirmed COVID-19 (23 pregnant and 8 non-pregnant women) between 1 September 2020 and 30 September 2020). The existence of syndrome coronavirus 2 (SARS-CoV-2) in vaginal fluid samples was used to determine evidence of genital transmission of the virus. A clinical laboratory procedure, including taking blood samples, IgG/IgM Rapid Test Cassette was performed to validate SARS-CoV-2 infection. Vaginal swabs were retrieved from SARS-CoV-2 positive patients between seven and 10 days of onset. Swabs were inserted two or three centimetres into the vagina and rotated three or five times. The swabs were immediately sent to the lab for RT-PCR, and the patients' COVID-19 status was verified. The real-time Polymerase Chain Reaction (BIORON Diagnostics GmbH's - RealLine SARS-CoV-2 (B-Format) BI1020-96 Tests). Results: Patients' vaginal fluids tested negative for SARS-CoV-2. Patients who tested positive for SARS-CoV-2 had normal platelet counts. Discussion: Our findings indicate that SARS-2 virus was not present in the vaginal fluid of the 31 patients, meaning that sexual transmission of SARS-CoV-2 is unlikely.